Development of an MR seat suspension with self-powered generation capability. (11th July 2017) - Sun, S S; Ning, D H; Yang, J; Du, H; Zhang, S W; Li, W H; Nakano, M
Abstract: This paper proposes a self-powered magnetorheological (MR) seat suspension on the basis of a rotary MR damper and an electromagnetic induction device. By applying the self-powering component to the MR seat suspension, the operation cost of the semi-active seat is much cheaper because no external energy is required to control the MR damper. In this paper, the structure, design and analysis of the seat suspension were presented following the introduction section. The property tests of the self-powered seat suspension were conducted using an MTS machine. A robust control algorithm was developed to control the self-powered MR seat suspension and the vibration attenuation performance of the seat suspension was tested under two different vibration excitations, i.e. harmonic excitation and random excitation. The testing result verifies that the self-powered MR seat suspension under proper control can improve the ride comfort for passengers and drivers.